Subky Latif: Istimewa terkenang - Subky Latif; Majdan Yahya (Kuala Lumpur : Media Icon, 2009)
Socio-political issues in Malaysia ; collected articles.
Keywords: Malaysia -- Politics and government; Malaysia -- Social conditions